Manajemen Strategik Pembentukan Karakter Ekoteologi Siswa Sekolah Alam Baturraden Banyumas - Syahriyah, Eri; Ulum, Iftah Bahrol Ulum; Khatin, Lilih Solih; Muflihin, Muh. Hizbul (Universitas Pakuan, 2025)
This study aims to analyze the strategic management of ecotheological character formation among students at Sekolah Alam Baturraden, Banyumas. The research is motivated by the importance of character education that integrates religious values and environmental awareness as a response to ecological crisis. The research method uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. Research subjects include teachers, learning facilitators, and students of Sekolah Alam Baturraden. Data analysis was conducted through data reduction, data presentation, and conclusion drawing with validity testing using source and method triangulation. The results show that strategic management of ecotheological character formation is implemented through five stages: situation analysis based on natural environment potential, formulation of strategic goals oriented towards holistic character, development of nature-based learning strategies integrated with religious values, consistent implementation through outdoor learning and ecological habituation, and continuous evaluation based on students' attitude and behavior development. This study confirms that nature-based strategic management plays an important role in systematically and sustainably shaping students' ecotheological character.